Utilization of prostate brachytherapy for low risk prostate cancer: Is the decline overstated? - Safdieh, Joseph; Wong, Andrew; Weiner, Joseph P.; Schwartz, David; Schreiber, David (Journal of Contemporary Brachytherapy, 2016)
Purpose : Several prior studies have suggested that brachytherapy utilization has markedly decreased, coinciding with the recent increased utilization of intensity modulated radiation therapy, as well as an increase in urologist-owned centers. We sought to investigate the brachytherapy utilization in a large, hospital-based registry. Material and methods: Men with prostate cancer diagnosed between 2004-2012 and treated with either external beam radiation and/or prostate brachytherapy were abstracted from the National Cancer Database. In order to be included, men had to be clinically staged as T1c-T2aNx-0Mx-0, Gleason 6, PSA ≤ 10.0 ng/ml. Descriptive statistics were used to analyze brachytherapy utilization over time and were compared via χ2. Multivariate logistic regression was used to assess for covariables associated with increased brachytherapy usage. Results : There were 89,413 men included in this study, of which 37,054 (41.6%) received only external beam radiation, and 52,089 (58.4%) received prostate brachytherapy. The use of brachytherapy declined over time from 62.9% in 2004 to 51.3% in 2012 (p < 0.001). This decline was noted in both academic facilities (60.8% in 2004 to 47.0% in 2012, p < 0.001) as well as in non-academic facilities (63.7% in 2004 to 53.0% in 2012, p < 0.001). The decline was more pronounced in patients who lived closer to treatment facilities than those who lived further. The use of intensity modulated radiation therapy increased during this same time period from 18.4% in 2004 to 38.2% in 2012 (p < 0.001). On multivariate analysis, treatment at an academic center, increasing age, decreasing distance from the treatment center, and years of diagnosis from 2006-2012 were significantly associated with reduced brachytherapy usage. Conclusions : In this hospital-based registry, prostate brachytherapy usage has declined for low risk prostate cancer as intensity modulated radiation therapy usage has increased. However, it still remains the treatment of choice for 51.3% of patients as of 2012.